Bulgaria : Issues in Intergovernmental Relations - World Bank (Washington, DC, 2013)
Municipalities play a large role in the Bulgarian public sector. They provide primary and secondary education. They own and operate about one-third of the hospitals in the country. Until 2003, they administered all the major social assistance programs (except pensions and unemployment insurance). The municipalities of larger cities own (wholly or partially) the water companies operating within their territories. Throughout the 1990's and into the first years of the present decade, problems in the structure of intergovernmental relations undermined efforts to achieve efficiency in public service provision and generate savings for investment in public utilities. Persistent deficits and bailouts undermined fiscal stability at both the central and local levels. A fundamental reform in intergovernmental fiscal relations went into effect in 2003. This has addressed many, although not all, of these problems. This report evaluates the reform, identifies major remaining issues, and recommends means to resolve them. The report is structured as follows: After the Introduction, which discusses existing government boundaries, functions, regulation, and revenues, Section 1 parses the issues regarding unfounded mandates, arrears, and fiscal autonomy; incentives to overstaffing; arbitrary disparities in per capita revenues; and infrastructure decline. Section 2 analyzes the 2003 Reform. Section 3 examines what remains to be done immediately and in the long-term.